Alpha-synuclein oligomers alter the spontaneous firing discharge of cultured midbrain neurons - Tomagra, Giulia; Franchino, Claudio; Cesano, Federico; Chiarion, Giovanni; de lure, Antonio; Carbone, Emilio; Calabresi, Paolo; Mesin, Luca; Picconi, Barbara; Marcantoni, Andrea; Carabelli, Valentina (Frontiers in Cellular Neuroscience, 2023)
The aim of this work was to monitor the effects of extracellular alpha-synuclein on the firing activity of midbrain neurons dissociated from substantia nigra TH-GFP mice embryos and cultured on microelectrode arrays (MEA). We monitored the spontaneous firing discharge of the network for 21 days after plating and the role of glutamatergic and GABAergic inputs in regulating burst generation and network synchronism. Addition of GABAA, AMPA and NMDA antagonists did not suppress the spontaneous activity but allowed to identify three types of neurons that exhibited different modalities of firing and response to applied L-DOPA: high-rate (HR) neurons, low-rate pacemaking (LR-p) and low-rate non-pacemaking (LR-np) neurons. Most HR neurons were insensitive to L-DOPA, while the majority of LR-p neurons responded with a decrease of the firing discharge; less defined was the response of LR-np neurons. The effect of exogenous alpha-synuclein (alpha-syn) on the firing discharge of midbrain neurons was then studied by varying the exposure time (0-48 hours) and the alpha-syn concentration (0.3-70 microM), while the formation of alpha-syn oligomers was monitored by means of AFM. Independently of the applied concentration, acute exposure to alpha-syn monomers did not exert any effect on the spontaneous firing rate of HR, LR-p and LR-np neurons. On the contrary, after 48 hours exposure, the firing activity was drastically altered at late developmental stages (14 DIV neurons): alpha-syn oligomers progressively reduced the spontaneous firing discharge (IC50= 1.03 microM), impaired burst generation and network synchronism, proportionally to the increased oligomer/monomer ratio. Different findings were found on early-stage developed neurons (9 DIV), whose firing discharge remained unaltered, regardless of the applied alpha-syn concentration and the exposure time. Our findings unravel, for the first time, the variable effects of exogenous α-syn at different stages of midbrain network development and provide new evidence for the early detection of neuronal function impairment associated to aggregated forms of α-syn.